2019
DOI: 10.1038/s41598-019-55474-3
|View full text |Cite
|
Sign up to set email alerts
|

Murine infection with bioluminescent Leishmania infantum axenic amastigotes applied to drug discovery

Abstract: Leishmaniasis is an important vector-borne neglected tropical disease caused by Leishmania parasites. Current anti-Leishmania chemotherapy is unsatisfactory, justifying the continued search for alternative treatment options. Herein, we demonstrate that luciferase-expressing Leishmania infantum axenic amastigotes, unlike promastigotes, are highly infectious to BALB/c mice and thus generate a robust bioluminescent signal in target organs, such as the liver and the spleen, as early as two weeks after infection. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…The data confirmed that there was no sterile cure as previously described in mice. Therefore, the next question that came up was whether those parasites still remaining in the organs could generate a new infection in an immunocompromised scenario. However, immunosuppression after treatment with CPP did not show any significant change in the parasitic load of these animals.…”
Section: Discussionsupporting
confidence: 73%
“…The data confirmed that there was no sterile cure as previously described in mice. Therefore, the next question that came up was whether those parasites still remaining in the organs could generate a new infection in an immunocompromised scenario. However, immunosuppression after treatment with CPP did not show any significant change in the parasitic load of these animals.…”
Section: Discussionsupporting
confidence: 73%
“…As compound levels may vary between different tissues, there is thus a risk of poor translation of pharmacokinetics and pharmacodynamics from mice to humans. The development of a bioluminescent mouse model of visceral leishmaniasis for drug screening has overcome this potential weakness in drug efficacy assessment in mice, enabling investigation of drug efficacy for liver, spleen and bone marrow parasites within 2 weeks of infection 138 . A bioluminescent mouse model for systematic screening of vaccines for visceral leishmaniasis is also now available 139 .…”
Section: Key Challenges and Solutionsmentioning
confidence: 99%
“…L. infantum promastigotes zymodeme 1 (MHOM/TN/80/IPT1 MON1), were used to infect mice. [ 32 ] The Leishmania strain, taken from the collection of the National Reference Center for Leishmaniasis, was grown in RPMI–PY medium, which consisted of RPMI 1640 (Sigma R0883) supple‐ mented with equal volume of Pepton‐yeast medium. [ 33 ] The promastigotes of the stationary phase were collected by centrifugation, washed in 0.3% NaCl, and counted in Bürker's chamber.…”
Section: Methodsmentioning
confidence: 99%